How CEOs can increase public engagement via microblogs: the role of CEO gender and content orientation - Wu, T; Reynolds, J; Schlegelmilch, BB; Wu, J (Wiley, 2024)
In the social media era, Chief Executive Officers (CEOs) are increasingly using microblogging sites to communicate with the public. Drawing on schema-congruity theory and gender egalitarianism, we investigate how CEO gender and work–life content orientation interact to influence public engagement with CEOs on microblogs. Using China as our research setting, we conduct a content analysis of data collected from 63 high-profile CEOs’ microblogs and four laboratory studies with some 2000 respondents. Our results show that for female CEOs, work-related content leads to greater engagement than life-related content; for male CEOs, the effect is reversed. We find that such outcomes are driven by the incongruity between stereotypical gender roles and content orientation, which enhances perceived novelty and audience interest, thus leading to greater engagement. This effect diminishes when the audience has a very high or very low perception of gender equality in their society; or when the audience supports male privilege values personally. Our research provides new theoretical insights for online leadership communication, public engagement and gender research. It also offers useful managerial guidance for executives to effectively leverage the capabilities of social media in engaging with the public.